2022
DOI: 10.3892/ol.2022.13476
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‑associated macrophage‑derived exosomes promote EGFR‑TKI resistance in non‑small cell lung cancer by regulating the AKT, ERK1/2 and STAT3 signaling pathways

Abstract: The evolutionary properties of organisms lead to the issue of targeted drug resistance. Numerous clinical trials have shown that tumor-associated macrophages (TAMs) in patients with lung cancer adversely affect the clinical efficacy of epithelial growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs). However, the mechanism by which TAMs influence the tumor cell response to TKIs remains unclear. The aim of the present study was to investigate the influence of TAM-derived exosomes on the sensitivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…These findings indicate a proinflammatory status induced by SIRT. Immune cell-derived EVs play crucial roles in intercellular communication and regulation of specific mechanisms of both adaptive and innate immune responses [42][43][44]. Similar to our results, previous research by Tung et al demonstrated the influence of EVs on dendritic cell activity and mobility through the study of dendritic cell interaction with exosomes derived from regulatory T cells (Tregs).…”
Section: Discussionsupporting
confidence: 90%
“…These findings indicate a proinflammatory status induced by SIRT. Immune cell-derived EVs play crucial roles in intercellular communication and regulation of specific mechanisms of both adaptive and innate immune responses [42][43][44]. Similar to our results, previous research by Tung et al demonstrated the influence of EVs on dendritic cell activity and mobility through the study of dendritic cell interaction with exosomes derived from regulatory T cells (Tregs).…”
Section: Discussionsupporting
confidence: 90%
“…Third, macrophages play a significant role in promoting chemotherapy resistance or radiation resistance in lung cancer cells through release of exosomes. For instance, the resistance of non-small cell lung cancer cells to epidermal growth factor receptor (EGFR)-targeted drugs could be attributed to the reactivation of AKT, ERK1/2, and signal transducer and activator of transcription 3 (STAT3) signaling pathways facilitated by exosomes released from macrophages ( Yuan et al, 2022 ). Moreover, M2 macrophages can activate the MAPK signaling pathway via exosomes, leading to resistance against the EGFR-targeted drug osimertinib ( Wan et al, 2022 ).…”
Section: Exosomes Are Involved In Macrophage-mediated Formation Of Th...mentioning
confidence: 99%
“…On the other hand, exosomes released by macrophages themselves are also relevant, it was found that M2 TAMs secrete exosomes containing miR-155 and miR-196a-5p that can promote EMT, cell migration, cell invasion and cell viability in NSCLC ( 68 ). TAM-derived exosomes can also favor EGFR-TKI resistance in NSCLC via activation of AKT, ERK1/2 and STAT3 signaling pathways ( 69 ). On the contrary, macrophages themselves and other immune cells, even some diseased cells, can polarize the naïve macrophages via exosomes toward a M1 phenotype ( 70 ).…”
Section: Exosome-mediated Communication Network Between Immune and Lu...mentioning
confidence: 99%